Structural and Spatial Analysis of the Mosques of the Architect Sinan with Hexagonal and Octagonal Baldachin Systems - Erarslan, Alev (Journal of History Culture and Art Research, 2021)
The master architect of the Ottoman era, Architect Sinan, created and left behind a wide range of structural typologies. The most numerous of Sinan’s works were his mosques. The features defining the layout plan of Sinan’s mosques are the central domed baldachin and the characteristics of the structure on which the baldachin rests. Sinan made use of multiple support systems of sometimes four, six or eight elements in his system of dome structures, planning the layouts of his mosques around the framework of these systems. Sinan handled each of his domed and multiple pillar-supported central baldachin in different ways in terms of both the foundation of the baldachin and of the side galleries, creating in this group of structures a “Sinan style.” This paper is an attempt to make a comparative analysis of the organization of the domed central baldachin constituting the main space of the mosques of Architect Sinan, which is part of a hexagonal and octagonal baldachin system with multiple supports forming the central nucleus of the mosque, and of the side galleries, addressing the relationships between baldachin, structures, dome and galleries.